Characterisation of redox states of metal-organic frameworks by growth on modified thin-film electrodes - Mitra, Tamoghna; Moreau, Florian; Nevin, Adam; Perotto, Carlo U.; Summerfield, Alex; Davies, E. Stephen; Gibson, Elizabeth; Easun, Timothy L.; Schröder, Martin (Royal Society of Chemistry, 2018)
The application of metal-organic framework (MOF) materials in electrochemical and electrochromic devices remain rare. One of the main reasons for this is the inability to readily access their detailed electrochemistry. The inherent insolubility of these materials does not allow interrogation by traditional solution-based electrochemical or spectroscopic methods. In this study, we report a straightforward alternative approach to the spectroelectrochemical study of MOFs. We have used two systems as exemplars in this study, MFM-186 and MFM-180. The method involves chemical modification of a working electrode to attach MOF materials without using corrosive reagents such as inorganic acids or bases which otherwise could limit their application in device development. MFM-186 demonstrates the formation of a stable radical species [MFM-186]●+ on electrochemical oxidation, and this has been characterised by electrochemical, spectroelectrochemical and EPR spectroscopic techniques coupled to DFT analysis.